THE ROLE OF SHORT VIDEO CONTENT IN FOREIGN LANGUAGE TEACHING - Rakhmonkulova Dilshoda Murodkuziyevna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
This article explores the role of short video content in foreign language teaching. With the rapid development of digital technologies and social media platforms, short videos have become an effective educational tool. The study examines their impact on learners' motivation, comprehension, and language acquisition. The findings suggest that short video content enhances engagement, improves listening skills, and facilitates contextual learning.